SEBARAN SITUS PRA SRIWIJAYA DI RAWA PASANG SURUT: KAJIAN ARKEOLOGI RUANG DI KAWASAN KARANGAGUNG TENGAH, SUMATERA SELATAN - Nurhadi Rangkuti (BRIN, 2014)
Archaeological research can not be separated from the three dimensions of archeology: form, space and time. Spatial dimensionÂ is essential in archeology that covers all phases of archaeological research (theory, method, practice). Collection, analysis, interpretation and presentation of archaeological data should be actively and creatively covered in the dimension of space, was realized in the form of a map. In the development of the map are integrated with other graphical data and databases, known as Geographic Information System.Â Study of spatial Archaeology in Karangagung Tengah conducted to determine the distribution pattern of the site and what factors influence the formation of the pattern. Archaeological sites scattered in the edges of tidal rivers with access to the Lalan River and Sembilang River which empties into the Strait of Bangka. Distribution of these sites mapped to the benefit of further research and reference to delineate the Karangagung Tengah zoning for conservation purposes.